Analisis Budaya Jepang dalam Buku Goodbye, Things Hidup Minimalis Ala Orang Jepang Oleh Fumio Sasaki - Hasibuan, Sekar Fatinah; Alfarisy, Fitri (KIRYOKU, 2024)
Lifestyle is a set of behaviours that are meaningful to the individual and others at a particular time and place, including social relationships, consumption of goods, entertainment, and clothing. Minimalism is the act of reducing things to make room for the more important things in life. A minimalist lifestyle is influenced by a consumptive lifestyle by reducing the items owned. Japanese minimalism has a rich history and is linked to cultural and philosophical traditions. A minimalist lifestyle is characterised by anti-consumerist attitudes and behaviours. A minimalist lifestyle offers many wellbeing benefits, including happiness, life satisfaction, meaning, and better personal relationships. Practising a minimalist lifestyle can be manifested by problem-avoiding behaviours, being content with enough possessions, and thinking carefully before making new purchases. The benefits of living a minimalist lifestyle range from environmental sustainability to mental health. This research aims to understand how Fumio Sasaki represents Japanese culture through the theme of minimalism and identify the Japanese cultural values reflected in this book with a qualitative method by thoroughly describing the data obtained during the research process. This research uses a literature approach by referring to theories obtained from literature in the form of books and journals as the main source and the literature.